Study of Morphology, Nutrition and Bioactive Compounds at Two Accessions Marigold (Tagetes Erecta) in Kepahiang Regency - Rita, Wismalinda; Neli Definiati; Rita Zurina; Edi Susilo; Parwito (PT FORMOSA CENDEKIA GLOBAL, 2024)
Marigold (Tagetes erecta) is an ornamental herbaceous and medicinal plant that is easily cultivated, so many are found at various heights, such as in Kepahiang Bengkulu regency, Indonesia. In addition, marigolds contain nutrients and bioactive compounds that have yet to be fully utilized. This study aims to identify the morphology, nutrients and bioactive compounds of marigold flowers in Kepahiang district of Bengkulu, Indonesia. The study was conducted using a purposive sampling survey method by conducting non-experimental descriptive observations. Sampling locations were conducted around Kepahiang regency. The variables observed were morphological identification, nutrient content and bioactive compounds. Two accessions are found: marigold flowers with small petals of orange and marigold flowers with small petals of yellow. Orange marigold flowers with small petals-shaped protein (10.51%) are higher than the small yellow marigold (9.49%), while the protein content of leaves (5.96%) is lower than the protein marigold flowers. Small-sized orange Petals marigold flowers have a higher carotenoid content (166.41 mg/kg) than small-sized yellow petals flowers (85.89 mg/kg). But compared to flowers, marigold leaves have a higher chlorophyll content (246.93 mg/kg). Marigold flower with orange petals in a small shape has the best nutritional and bioactive compounds content for poultry feed